Analysis of Hot Spots in Watershed Runoff Generation and Concentration Based on Bibliometrics - HU Jinhui; SUN Yingna; WANG Ning; LI Zan (Renmin Zhujiang)
At present,the CiteSpace is rarely applied in the field of hydrology.Compared with other similar applications,this software can analyze data easily and generate visual map flexibly.Based on that,using CiteSpace to analyze the hot spots of watershed runoff generation and concentration can provide some references to scholars.Through the CNKI database,1 046 journals and academic papers from 1999 to 2020 are retrieved with “runoff generation and concentration”,“model” and “flood” as the subject terms.Based on the analysis functions of CNKI and CiteSpace,the results show that:among the Keyword co-occurrence map,the domestic hot spots in the field of watershed runoff generation and concentration include “Flood Forecast”,“Distributed Hydrological Model”,“Xin'an River Model”,“Urbanization”,“SWMM Model”,“Underlying Surface”,etc.By using the clustering function,the relevant research can be divided into “Flood Forecast”,“Control of Urban Flood”,“Geographic Information System”,and “Flood Disaster”.According to the clustering timeline diagram,“Simulation of Runoff Generation and Concentration in Hydrological Cycle” and “Simulation of Urban Flood Control Construction by Low-impact Development Concepts and SWMM Model” are current hot spots.Finally,detailed analysis related to those two hot spots are presented.